2007
DOI: 10.2151/jmsj.85a.325
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Indian Summer Monsoon 2004-Observed and Model Forecasts

Abstract: The observed and the model forecast rainfall and other atmospheric fields are compared To determine the skill of the National Centre for Medium Range Weather Forecasting (NCMRWF) model in forecasting precipitation and circulation features over India, we compared observed and forecast rainfall and other atmospheric fields for the boreal summer monsoon season of 2004. This season was an important period within the period 4 of the Coordinated Enhanced Observing Period (CEOP). For comparison of observed rainfall w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…PSCF was calculated at an altitude corresponding to that of precipitable cloud formation during the SW monsoon in the northern Arabian Sea region. Results from studies characterizing the SW monsoon at several locations in the Arabian Sea, and along its coast, suggested that 1,500 m is the average height for the formation of precipitable clouds (e.g., Rao and Tamin 1995;Rajkumar et al 1996;Bhaskaran et al 1998;Fleitmann et al 2003;Basu and Iyengar 2007).…”
Section: Application Of Pscf For Identification Of Geographical Sourcmentioning
confidence: 99%
“…PSCF was calculated at an altitude corresponding to that of precipitable cloud formation during the SW monsoon in the northern Arabian Sea region. Results from studies characterizing the SW monsoon at several locations in the Arabian Sea, and along its coast, suggested that 1,500 m is the average height for the formation of precipitable clouds (e.g., Rao and Tamin 1995;Rajkumar et al 1996;Bhaskaran et al 1998;Fleitmann et al 2003;Basu and Iyengar 2007).…”
Section: Application Of Pscf For Identification Of Geographical Sourcmentioning
confidence: 99%